Sea Level Rise in New Zealand: The Effect of Vertical Land Motion on Century‐Long Tide Gauge Records in a Tectonically Active Region. Issue 1 (21st January 2020) - Denys, Paul H.; Beavan, R. John; Hannah, John; Pearson, Chris F.; Palmer, Neville; Denham, Mike; Hreinsdottir, Sigrun
Abstract: Historically tide gauge (TG) data have been used to estimate global sea level rise. Critical to the analysis of TG records is the assumption that the TG sites are stable and not affected by vertical land motion (VLM). We analyze century‐long TG records from New Zealand that have been affected by VLM due to both major and transient earthquake events at a regional level as well as local instabilities. Using combined GPS and precise leveling, we estimate relative VLM between the GPS and TG of up to 1 mm/year. Based on 15–20 years of GPS data, the effect of seismic activity and slow slip events has uplifted sites by up to 0.8 mm/year on average in Wellington and Dunedin. Updated estimates of long‐term relative sea level (RSL) at four New Zealand TGs, as well as an estimate of RSL at a new fifth TG (New Plymouth), are determined using data through 2013—an additional 13 years compared to the previous study. The VLM corrected RSL rates gives our best estimate absolute sea level of +1.45 ± 0.28 mm/year (1891−2013). It is important that absolute sea level derived from RSL rates include realistic estimates of VLM, especially at TG sites that are close to plate boundaries, located in seismically active regions, affected by glacial isostatic adjustment, land ice loss, or gas/oil/water extraction. Key Points: We use 15 years of continuous GPS data to estimate vertical land motion and use precise leveling data to determine the stability of benchmark networks The vertical land motion also includes an estimate of accumulated seismic events including postseismic deformation and slow slip events The vertical land motion corrected trend gives a sea level rate of +1.45 ± 0.36 mm/year (1891−2013)